ECONOMIC POLICIES ON RICE COMMODITY AND WELFARE - Muhammad Asaad (Economic Journal of Emerging Markets, 2010)
This study aims at determining the impacts of economic policies on rice and welfare in Indonesia.It estimates a simultaneous equation model with two-stage least squares method, using secondarydata from 1979 until 2008. The simulation of partial policy will be a trade-off for the producers andconsumers of rice. The policy of the floor grain price is still needed to respond to the increasedproduction of rice. The paper suggests that if the input subsidy is taken out, it should be preferablyfollowed by the increase in output, and at least, the rising percentage should be in the same numberso that the policy will be better off.Keywords: Welfare, trade-off, better-off, simultaneous equation modelJEL classification numbers: Q13, Q18